Dynamics and Strategies of Law Enforcement of Money Laundering Offences in Indonesia: Dinamika dan Strategi Penegakan Hukum Tindak Pidana Pencucian Uang di Indonesia - Fhatnur, Yoga Sugama Ali (Universitas Muhammadiyah Sidoarjo, 2024)
General Background Money laundering is a transnational financial crime that threatens economic stability, involving illicit financial flows disguised as legitimate transactions. Specific Background In Indonesia, the increasing complexity of money laundering is driven by financial digitalization and globalization, enabling criminals to exploit regulatory loopholes. Knowledge Gap Despite the existence of anti-money laundering (AML) regulations, enforcement effectiveness and adaptation to new financial technologies remain challenging. Aims This study aims to analyze the dynamics of money laundering cases in Indonesia, evaluate the effectiveness of existing legal frameworks, and identify areas for regulatory improvement. Results Findings indicate that while Indonesia has made progress in AML enforcement, legal loopholes, limited cross-border cooperation, and emerging financial technologies hinder optimal prevention efforts. Novelty This study provides a comprehensive analysis of recent judicial decisions (2015–2020) and assesses Indonesia’s compliance with global AML standards. Implications Strengthening financial intelligence, international collaboration, and regulatory adaptation to digital financial innovations are crucial for enhancing AML measures and mitigating economic risks. Highlights: Money laundering in Indonesia is evolving due to digital financial advancements and globalization. Legal loopholes and weak cross-border cooperation hinder effective enforcement. Strengthening financial intelligence and regulations is crucial for economic stability. Keywords: Money Laundering Crime, Law Enforcement, Digital Finance